Analysis of UI/UX design in digital wallet applications using the heuristic evaluation method - Setiaji Setiaji; Allifia Annisa (Jurnal Scientia, 2024)
Digital wallets have become a crucial solution in the financial industry, facilitating transactions efficiently and conveniently. However, the success of digital wallets depends on their functionality and the user experience they provide. Therefore, this research aims to evaluate the user interface (UI/UX) design of two popular digital wallet applications in Indonesia, namely Ovo and Dana. The research methodology employed a combination of user experience testing and Heuristic Evaluation. User experience testing involved real users who use various popular digital wallet applications in Indonesia. Data were collected through questionnaires distributed to Ovo and Dana users. With a sample size of 102 respondents, the findings reveal a substantial surge in adopting digital wallets in Indonesia, with Ovo and Dana emerging as the preferred choices among users. Despite their popularity, the study identified several user issues, including navigation difficulties, confusion in account settings, and a need for clarity in certain features. Heuristic Evaluation was utilized to analyze both applications UI/UX designs, identifying strengths and weaknesses. The evaluation results provided in-depth insights into how these applications adhere to established UI/UX design principles. Based on these findings, recommendations are proposed to improve the UI/UX. The primary contribution of this research is to offer a profound understanding of the UI/UX design of digital wallet applications, guiding developers to enhance their designs, identify areas for improvement, and ensure that users have a satisfying and efficient experience when using digital wallets.